Identificación de la vía de señalización y las moléculas del suero sanguíneo implicadas en el aumento de la virulencia de Mucor lusitanicus - Alejandre Castañeda, Viridiana (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Mucor lusitanicus is a dimorphic Mucoral fungus capable of growing as avirulent yeasts, associated with a fermentative metabolism; or as mycelium, with a virulent phenotype by increasing its oxidative metabolism. Some Mucorales cause mucormycosis, a rare opportunistic infection but associated with high mortality rate. M. lusitanicus is a biological model to study this infection; it has been described that human blood serum (serum) stimulates its mycelial growth and virulence. On the other hand, heterotrimeric G proteins (HGPs) regulate the cAMP-PKA (protein kinase A) pathway, which regulates mycelial growth and virulence. M. lusitanicus has 18 HGP subunits: alphas (Gpa1–Gpa12), betas (Gpb1– Gpb3) and gammas (Gpg1–Gpg3). Gpb1, Gpa11 and Gpa12 stimulate mycelial growth by repressing PKA activity. M. lusitanicus has 4 regulatory (R) and 10 catalytic (C) subunits, PkaR1 promotes mycelial growth by repressing the PKA pathway. Serum stimulates the virulence of Mucorales by increasing mitochondrial oxidative metabolism; however, the identity of the proteins involved in serum perception and the virulence factor involved in this process were unknown. The aim of this study was to describe in M. lusitanicus the identification of the signaling pathway involved in the increase of serum-induced virulence, as well as the virulence-inducing molecules. Mutants in the cAMP-PKA-GPH pathway were used, demonstrating that the GPCR2 receptor transduces the signal through the Gpb1-Gpg1 dimer generating the repression of the adenylate cyclase, Cyr1, which resulted in low levels of cAMP through PkaR1, resulting in the stimulation of mycelial growth, mitochondrial activity, virulence and secretion of the toxic factor rhizoferrin.

Mucor lusitanicus es un hongo mucoral dimórfico capaz de crecer como levaduras avirulentas, asociadas a un metabolismo fermentativo; o como micelio, de fenotipo virulento al incrementar su metabolismo oxidativo. Algunos Mucorales causan la mucormicosis, infección oportunista poco común pero asociada a una alta mortalidad. M. lusitanicus es un modelo biológico para estudiar esta infección, se ha descrito que el suero sanguíneo humano (suero) estimula su crecimiento micelial y virulencia. Por otra parte, las proteínas G heterotriméricas (PGH) regulan la vía AMPc-PKA (proteína cinasa A), la cual regula el crecimiento micelial y la virulencia. M. lusitanicus posee 18 subunidades PGH: alfas (Gpa1–Gpa12), betas (Gpb1–Gpb3) y gamas (Gpg1–Gpg3). Gpb1, Gpa11 y Gpa12 estimulan el crecimiento micelial, reprimiendo la actividad de PKA. M. lusitanicus posee 4 subunidades regulatorias (R) y 10 catalíticas (C), PkaR1 promueve el crecimiento micelial reprimiendo la vía PKA. El suero estimula la virulencia de los Mucorales al incrementar el metabolismo oxidativo mitocondrial; sin embargo, la identidad de las proteínas implicadas en la percepción del suero y el factor de virulencia de M. lusitanicus involucrados eran desconocidas. El objetivo de este estudio fue describir en M. lusitanicus la vía de señalización implicada en el aumento de la virulencia inducida por el suero, así como las moléculas del suero inductoras de la virulencia. Se usaron mutantes en la vía AMPc-PKAPGH, demostrando que el receptor GPCR2 transduce la señal a través del dímero Gpb1-Gpg1 generando la represión del adenilato ciclasa, Cyr1, lo que resultó en bajos niveles de AMPc a través de PkaR1, resultando en la estimulación del crecimiento micelial, la actividad mitocondrial, la virulencia y la secreción del factor tóxico rizoferrina.
Instituto de Investigaciones Químico Biológicas. Doctorado en Ciencias en Biología Experimental
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19021; info:eu-repo/classification/cti/6; IIQB-R-D-2024-1675; Virulencia; AMPc-PKA; Suero sanguíneo